Economic Analysis of Dairy Cattle Farms under Town Milk Supply Scheme in Jorhat District of Assam - Priyamvada, Shweta; Mishra, B K (Indian Journal of Dairy Science, 2019)
Dairy development has assumed significant importance in the rural economy of India due to its immense potential for supplementing income and employment generation for the rural people. Recently, under the Town Milk Supply Scheme, Government of Assam has attempted to increase the milk production under organized sector. Present study is an attempt to study the economics of organized dairy cattle farms in Jorhat district of Assam started under the scheme. The study was done by selecting 100 commercial dairy farmers under organized dairy sector in Jorhat district of Assam. In the study area 81 dairy farmer found to be small category, 10 dairy farmers were identified to be in medium category and nine dairy farmers were in large category of dairy farmer. The total milk production in 100 sample dairy farms was reported as 3445 litres per day with average milk production of 8.79 litres per day per milch animal. The total milk production per day per farm in small dairy farms was observed as 21.57 litres, in medium dairy farms as 58.7 litres and in large as 123.44 litres. Overall the average milk production per farm in 100 sample households was estimated to be 34.45 litres per farm per day. With more than 94 percent of the investments the dairy cattleâ€™s especially the cross breed and Indian breed accounted for the maximum share of the investments. A return of Rs. 812.68 per farm per day in small category of dairy farms, Rs. 2210.85 per farm per day in medium category of dairy farms, Rs. 4497.81 per farm per day in large category of dairy farms was observed. The income from sale of milk constituted the maximum proportion of the income (more than 98 percent) in all the categories of the dairy farm. The returns from sale of manure/cow dung and male calves also contributed to the total income but in minimal way. It was observed that the profit per farm per day increased from Rs. 248.53 from small farms to Rs. 690.86 in medium farms to Rs. 773.9 in large dairy farms. Feed cost influence was positive and significant. Hence, increase in the use of feed would increase the revenue from dairy farms by 1.66 percent. Â